2022
DOI: 10.1002/alr.22952
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the patient experience of chronic rhinosinusitis with nasal polyposis: qualitative development of a novel symptom diary

Abstract: Background: This qualitative study assessed the experience of patients with chronic rhinosinusitis with nasal polyposis (NP) to inform the development of a novel symptom diary for clinical study use. Methods:Concept elicitation and cognitive interviews were conducted with patients who had a physician-verified diagnosis of NP and a history of intranasal corticosteroid use. Concepts were identified via open-ended and follow-up questions. Relative symptom/impact disturbance level was assessed using a scale of 0 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 21 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…Following regulatory guidelines, interviews of patients with CRSwNP established the content validity of this novel PRO tool. 10 The comprehensive psychometric analyses based on OSTRO data from over 500 screened patients demonstrated the reliability, construct validity, and ability to detect change in NPSD scores measuring single (NBS, NCS, and DSS) and combined (TSS) symptoms. Test-retest ICC values for NPSD scores ranged from 0.828 to 0.960, in line with values reported for other instruments such as the SNOT-22 test-retest reliability of 0.93 in patients with CRS.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Following regulatory guidelines, interviews of patients with CRSwNP established the content validity of this novel PRO tool. 10 The comprehensive psychometric analyses based on OSTRO data from over 500 screened patients demonstrated the reliability, construct validity, and ability to detect change in NPSD scores measuring single (NBS, NCS, and DSS) and combined (TSS) symptoms. Test-retest ICC values for NPSD scores ranged from 0.828 to 0.960, in line with values reported for other instruments such as the SNOT-22 test-retest reliability of 0.93 in patients with CRS.…”
Section: Discussionmentioning
confidence: 97%
“…7 However, these PRO measures were not specifically developed for patients with CRSwNP. 7 Recall periods in existing tools (eg, SNOT-22) might be too long to capture daily symptom variation, [8][9][10] potentially overlooking important day-to-day changes in symptoms induced by medical therapy. [11][12][13] A literature review of existing instruments indicated a gap for a novel, brief, daily PRO questionnaire developed specifically in CRSwNP to track changes in symptoms and impacts during clinical trials.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations